Comparisons of oxygen gradient ektacytometry parameters between sickle cell patients with or without α‐thalassaemia. (15th August 2021) - Boisson, Camille; Renoux, Céline; Nader, Elie; Gauthier, Alexandra; Poutrel, Solène; Rab, Minke; Fort, Romain; Bertrand, Yves; Stauffer, Emeric; Cannas, Giovanna; Kebaili, Kamila; Virot, Emilie; et al.
Summary: The present study tested the impact of α‐thalassaemia on oxygen gradient ektacytometry in sickle cell anaemia (SCA). Three SCA groups were compared: (i) no α‐thalassaemia (four α‐genes, n = 62), (ii) silent α‐thalassaemia (three α‐genes, n = 35) and (iii) homozygous α‐thalassaemia (two α‐genes, n = 12). Red blood cell (RBC) deformability measured in normoxia was not different between the three groups. The lowest RBC deformability reached at low oxygen partial pressure (pO2 ) was greater and the pO2 at which RBC started to sickle was lower in the two α‐genes group compared to the other groups. Our present study showed an effect of α‐thalassaemia on oxygen gradient ektacytometry in SCA.